Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar dalam Sub Materi Media Sosial di Kelas VII pada SMP Negeri 2 Darma - Fadhlurrohman, Fikri; Haerudin, Dodi Ahmad (Indo-MathEdu Intellectuals Journal, 2024)
The low learning outcomes of Information Engineering (ICT) students in grade VII of SMP Negeri 2 Darma are caused by several factors, including students who are less motivated to learn ICT and also the factor of teachers who still use conventional methods or lecture methods so that in the teaching and learning process students tend to be passive. This study aims to find out whether there is an influence of the Contextual Teaching and Learning (CTL) learning model on learning outcomes in social media sub-material in grade VII at SMP Negeri 2 Darma. The research approach used is a quantitative approach with an experimental research design type. The population in this study is 35 students with a sample of grade VII of SMP Negeri 2 Darma. The data collection technique uses a test. Data analysis using t-test. The results of the study showed that the pretest results had a mean of 46.42 and a posttest result of 68.71. Contextual Teaching and Learning (CTL) learning media has an influence on the learning outcomes of information technology (ICT) social media sub-materials. This is shown from the results of data analysis that the value of, t count = 10.911 > t table = 2.650, so that the hypothesis proposed in the study is accepted, so that there is an influence of the Contextual Teaching and Learning (CTL) learning model on learning outcomes in social media sub-material in grade VII at SMP Negeri 2 Darma